Design and Development of Ferry E-Ticketing System with QR Code based on IoT Technology - Ong, Yee Lin; Abdullah, Noryusliza (Applied Information Technology And Computer Science, 2023)
The objective of developing an IoT-based ferry e-ticketing system with QR is to digitalize a public transportation company's ticket selling business by reducing the time spent purchasing, and attempting to reduce human errors. This system is critical to improving top-line performance at Bahtera Ferry Services Sdn. Bhd. Using this technology, passengers can obtain real-time ticket information by visiting the company's website rather than contacting customer service. It makes things easier for customers while also saving the company money on making the call and printing all of the tickets on a single sheet of paper. The e-ticket will be generated instantly and emailed to the user after purchase. This system also includes a management system extension that makes it easier to manage all ticket, vessel, and website information. A computerised system, when compared to manual labour, may improve job efficiency by eliminating redundant effort. On the contrary, there are numerous public transportation ticketing solutions available today, but their services are unable to connect with the back-end database server to provide passengers with on-time verification and validation during the boarding session. This project is equipped with Arduino controller and IoT technology, allowing the use of a QR code scanner to retrieve a passenger's e-ticketing boarding details and validation in a split second using the Arduino controller linking with the back-end phpMyAdmin database to verify a passenger's boarding particulars and details. In a nutshell, the Eclipse PHP IDE and phpMyAdmin as the web server and database server were used to create this web-based ferry ticketing system as an intermediate level ticketing and boarding system.